Estudo fitoquímico de plantas das famílias Rutaceae e Meliaceae visando o isolamento de substâncias protótipos para o desenvolvimento de novos fármacos antichagásicos e antileischmanioses - Ambrozin, Alessandra Regina Pepe (2004)
This work involved the bioassay-guided study of Almeidea coerulea, A. rubra, Conchocarpus heterophyllus, Galipea carinata (Rutaceae), and Trichilia ramalhoi (Meliaceae). The bioassays were carried out with T. cruzi GAPDH and L. tarentolae APRT enzymes, and trypomastigote forms of T. cruzi as model assays. The results obtained with extracts and fractions showed that selected plants are promising source for the search of antiprotozoal compounds. Chemical investigation of active fractions (or extracts) allowed the isolation of 30 substances. Among them, 6 are described for the first time: an eudesmane sesquiterpene, pyranoflavones, a tetrahydrofuroquinoline alkaloid, an indolopyridoquinazoline alkaloid, an anthranilic acid derivative, and 1,5-diphenyl-1-pentanone; and 24 substances have already been described in the literature: β-sitosterol and stigmasterol, sitostenone, β-sitosteryl benzoate, lupeol, lupenone, flavone, 7-methoxyflavone, 5-hydroxyflavone, dictamine, kokusagine, skimmianine, δ-fagarine, isokokusagine, isoskimmianine, isodutaduprine, haplotusine, 1-methyl-2-phenyl-4-quinolone, arborinine, scoparone, scopoletin, marmesine, paprazine, N-transferuloyltyramine, and siringic acid. Among these substances, furoquinolone alkaloids isokokusagine and isoskimmianine were actives on the inhibition of APRT enzyme; marmesine was active on GAPDH enzyme; and haplotusine and the 1-methyl-2-phenyl-4-quinolone alkaloid showed significant trypanocidal activities. The biological results showed that a systematic investigation of active chemical classes is needed for determination of structure-activity relationship and obtaining more active substances, that could be used as targets for the development of new antichagasic and antileishmaniasis drugs.